Geometri Bintang Berotasi Pada Keadaan Ambang - Iwan Setiawan; Muhammad Farchani Rosyid (Institut Teknologi Bandung, 2010)
The mechanical equilibrium configuration of rotating stars is discussed through Roche model. In our study, the stars are assumed to rotate rigidly, while their geometry are determined by the use of their equipotential surfaces. The critical state is achieved by a rotating star, when its total gravitational force vanishes. There are two posibilities for a star to be in its critical state: either its effective gravitational force vanishes or it exceeds the Eddington limit. The meridional section of rotating stars of various masses and angular velocity are determined.